Exploring the contributing factors to the happiness index in the context of social environment - Titisari, Andari; Santoso, Michelle Nabillarisa Qori (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Happiness is a vital factor for well-being, and its measurement has become an important tool in assessing national prosperity. The United Nations' World Happiness Report ranks countries annually, and in 2024, Indonesia ranked 80th out of 143 countries. This study examines Indonesia's happiness index, focusing on the factors influencing happiness, such as life satisfaction, social support, and inequality, beyond just economic measures like GDP. Methods: The research used a descriptive qualitative method with a phenomenological approach. Data was gathered from the happiness index published by Indonesia's Central Statistics Agency, which includes nineteen indicators categorized into three dimensions: life satisfaction, feelings, and the meaning of life. These indicators were analyzed to determine their contribution to the national happiness index. Findings: The study found that happiness in Indonesia is influenced by more than just the nation's GDP. Factors such as education, health, poverty levels, the GINI index (income inequality), and social contributions like Zakat, Infaq, and Charity (ZIS) play significant roles. Higher levels of social support, as represented by ZIS, are linked to increased happiness, while income inequality, measured by the GINI index, can negatively impact happiness. Conclusion: The happiness index in Indonesia is shaped by a combination of economic, social, and health-related factors. While GDP is important, variables like education, health, and social support systems, including charitable activities, have a more direct impact on individual and collective happiness in Indonesia. Novelty/Originality of this Study: This study provides a deeper understanding of the multidimensional nature of happiness in Indonesia, highlighting the significance of social and economic factors beyond traditional measures such as GDP. It emphasizes the role of social support and the impact of inequality on happiness, offering insights into improving national well-being.